1996
DOI: 10.1038/ki.1996.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrapure and non-sterile dialysate on the inflammatory response during in vitro hemodialysis

Abstract: Several studies support the hypothesis that bacterial contamination of the dialysate stimulates the inflammatory response to hemodialysis (HD) and increases the long-term morbidity of HD patients; this phenomenon could also be modulated by the nature of the HD membrane. Therefore, this study was designed to compare the effects of non-sterile (NSBD, mean endotoxin content +/- SEM 97 +/- 22 EU/ml) and ultrapure bicarbonate dialysate (UPBD, sterile and pyrogen-free, obtained by ultrafiltration through polyamide) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 38 publications
2
49
0
2
Order By: Relevance
“…Furthermore, the amount of IL-1β appeared independent of the bacterial quality of the dialysate. Hence, in contrast with the changes in expression of cell surface molecules, cytokine release by dialyser-adherent cells appears to depend largely on the material of the device [35]. As for the latter finding, comparable data have been published recently [36].…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, the amount of IL-1β appeared independent of the bacterial quality of the dialysate. Hence, in contrast with the changes in expression of cell surface molecules, cytokine release by dialyser-adherent cells appears to depend largely on the material of the device [35]. As for the latter finding, comparable data have been published recently [36].…”
Section: Discussionsupporting
confidence: 71%
“…The origin of inflammation in these patients has not been clearly identified. It has been suggested that the dialysis procedure per se may account for the inflammation [6,7,8,9]. However, dialysis is unlikely to be solely responsible for this, as raised CRP levels are relatively common in patients with chronic renal failure (CRF) prior to the initiation of dialysis [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports [8, 10], we have shown that culture with CU membrane induces apoptosis in human monocytes. After 48 h of culture with the CU membrane, 47 ± 9% of the THP-1 cells undergo apoptosis (fig.…”
Section: Resultsmentioning
confidence: 99%
“…During hemodialysis with bioincompatible membranes such as Cuprophan (CU), activation of mononuclear cells results in cytokine release [1, 2, 3, 4], expression of adhesion molecules [5, 6, 7, 8], and formation of cell aggregates, and some cells undergo apoptosis [9, 10]. The mechanism(s) by which hemodialysis membranes induce mononuclear cell activation are not completely understood.…”
Section: Introductionmentioning
confidence: 99%